Rapid assessment of West Nile virus circulation in a German zoo based on honey-baited FTA cards in combination with box gravid traps - Fynmore, Noelle; Lühken, Renke; Maisch, Heike; Risch, Tina; Merz, Sabine; Kliemke, Konstantin; Ziegler, Ute; Schmidt-Chanasit, Jonas; Becker, Norbert (Parasites & Vectors, 2021)
BACKGROUND: For over a decade, monitoring of West Nile virus (WNV) in Germany has consisted of a bird monitoring programme as well as a mosquito-based surveillance programme employing CO₂-baited encephalitis vector surveillance (EVS) traps for mass trapping and screening of mosquitoes. In contrast to the EVS traps, the Reiter/Cummings type box gravid trap collects gravid female mosquitoes, which have already taken a blood meal, increasing the likelihood of being infected with pathogens. The traps can be equipped with a honey-baited Flinders Technology Associates® (FTA) card to encourage sugar feeding by the trapped mosquitoes. FTA cards contain nucleic acid preserving substances, which prevent the degradation of viral RNA in the expectorated mosquito saliva and allows for testing the card for flavivirus RNA. This study aimed to assess the suitability of the method for WNV surveillance in Germany as an alternative to previous methods, which are expensive, time-consuming, and predominantly target host-seeking populations less likely to be infected with WNV. METHODS: In the Thüringer Zoopark Erfurt, snowy owls (Nyctea scandiaca) and greater flamingos (Phoenicopterus roseus) died of WNV infections in July and August 2020. In response, five Reiter/Cummings type box gravid traps were positioned during the daytime on the 10th, 13th, and 16th of September in five different locations. The FTA cards and mosquitoes in the chamber were collected, kept in a cool chain, and further processed for virus detection using a modified generic flavivirus reverse transcription PCR. RESULTS: A total of 15 trappings during September collected a total of 259 female mosquitoes, 97% of which were Culex pipiens sensu lato, as well as 14 honey-baited FTA cards. Eight mosquitoes tested PCR-positive for WNV. Four FTA cards tested PCR-positive for mosquito-borne flaviviruses, two of which were confirmed as WNV, and the remaining two confirmed as Usutu virus. CONCLUSION: The suitability of the FTA cards in preserving viral RNA in the field and ...